Obstruction sleep apnoea and panic disorder - Vanek, Jakub; Belohradova Minarikova, Kamila; Prasko, Jan; Genzor, Samuel; Subova, Dana; Hodny, Frantisek; Pobeha, Pavol; Bocek, Jonas; Ociskova, Marie (Neuro-endocrinology letters, 2023)
OBJECTIVE: Both panic disorder (PD) and obstructive sleep apnea (OSA) are frequent conditions that can be comorbid. This article reviews the current state of knowledge about the comorbidity of PD and OSA and the effectiveness of therapy in patients with this comorbidity. METHOD: Articles obtained via PubMed and Web of Science search were selected; the publishing date was between January 1990 and December 2022. The applied search terms were: obstructive sleep apnea; panic disorder; CPAP; antidepressants; anxiolytics; antipsychotics. Eighty-one articles were chosen by primary search via keywords. After a complete assessment of the full texts, 60 papers were chosen. Secondary papers from the references of the primary documents were investigated, evaluated for suitability, and included in the list of documents (n = 18). Thus, seventy-eight papers were incorporated into the review article. RESULTS: Studies describe a greater prevalence of panic disorder in OSA patients. So far, there is no data on the prevalence of OSA in PD patients. Limited evidence is found regarding the influence of CPAP treatment on PD, and this evidence suggests that CPAP can partially alleviate PD symptoms. Medication used in PD treatment can significantly impact comorbid OSA, as explored in several studies. CONCLUSIONS: The relationship between the two conditions seems bidirectional, and it is necessary to assess OSA patients for comorbid panic disorder and vice versa. Both disorders can worsen the other and must be treated with a complex approach to ensure improvement in patients' physical health and psychological well-being.
Keywords: Panic Disorder; trvalý přetlak v dýchacích cestách; obstrukční spánková apnoe; Anti-Anxiety Agents; panická porucha; Humans; komorbidita; lidé; Comorbidity; Continuous Positive Airway Pressure; Sleep Apnea, Obstructive; anxiolytika